2006
DOI: 10.1158/0008-5472.can-05-2036
|View full text |Cite
|
Sign up to set email alerts
|

Soluble IGF2 Receptor Rescues Apc Min/+ Intestinal Adenoma Progression Induced by Igf2 Loss of Imprinting

Abstract: The potent growth-promoting activity of insulin-like growth factor-II (IGF-II) is highly regulated during development but frequently up-regulated in tumors. Increased expression of the normally monoallelic (paternally expressed) mouse (Igf2) and human (IGF2) genes modify progression of intestinal adenoma in the Apc Min/+ mouse and correlate with a high relative risk of human colorectal cancer susceptibility, respectively. We examined the functional consequence of Igf2 allelic dosage (null, monoallelic, and bia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 60 publications
3
41
0
1
Order By: Relevance
“…These results suggest that IGF-I acts on the tumor through an endocrine manner and that IGF-II acts mainly in an autocrine or paracrine manner in the vicinity of the tumors. These data are consistent with previous reports showing that liver-specific IGF-I deficiency reduces tumor progression in an orthotopic xenograft model (10) and that the soluble form of IGF-IIR produced constitutively in the intestine reduces intestinal polyp formation in Apc Min/+ mice (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that IGF-I acts on the tumor through an endocrine manner and that IGF-II acts mainly in an autocrine or paracrine manner in the vicinity of the tumors. These data are consistent with previous reports showing that liver-specific IGF-I deficiency reduces tumor progression in an orthotopic xenograft model (10) and that the soluble form of IGF-IIR produced constitutively in the intestine reduces intestinal polyp formation in Apc Min/+ mice (18).…”
Section: Discussionsupporting
confidence: 93%
“…Loss of imprinting of the IGF-II gene increases locally produced IGF-II concentration, which correlates with colorectal carcinogenesis (11)(12)(13)(14)(15). Some studies have shown that IGF-II modifies intestinal tumor growth in Apc Min/+ mice, a close genotypic and phenotypic model of human familial adenomatous polyposis, with genetically altered IGF-II expression (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Àm/+p mouse model can reverse the tumor-promoting effects of biallelic expression of Igf2 in vivo (16). Alternative approaches that target deregulation of the IGF system in tumors include interruption of ligand receptor interactions by increasing the supply of binding proteins, introducing either ligand-specific or receptor antibodies (20,52), expressing soluble and ligand binding forms of IGF1R (73), disruption of IGF1R receptor supply with RNA targeting (74), and inhibition of kinase activity of the IGF1R (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I can also antagonize the antiproliferative effects of cyclooxygenase-2 (COX-2) inhibitors (21). Soluble IGF-IIR salvages Apc (Min/þ) intestinal adenoma progression induced by loss of IGF-II imprinting (11). IGF-IR is also important for tumor maintenance in addition to carcinogenicity (22,23).…”
Section: Introductionmentioning
confidence: 99%